Analysis of Green Investment, Access to Clean Fuels, Green Jobs, Green Energy, and CO2 Emissions on Economic Growth and Welfare: An Empirical Study in Developing Countries - Sasana, Hadi; Khusniati, Navi'ah; Purnomo, Rochmat Aldy; Shafiai , Muhammad Hakimi Mohd (International Journal of Energy Economics and Policy, 2025)
The adoption of a sustainable economic model aims to enhance community well-being and promote social equity while minimising the potential for ecological harm. Economic development focused on a green economy is realised by minimising CO2 emissions through the reduction of fossil fuel consumption and the transition to renewable energy sources. This study aims to examine the effects of implementing a green economy, focussing on aspects such as renewable energy investment, renewable energy consumption, green jobs, and access to clean energy, on economic growth and overall welfare. The investigation took place across 10 developing nations, spanning the years 2015-2023. The analytical method employed was Generalised Least Squares (GLS). The findings indicate that environmentally sustainable investments contribute positively to economic growth in all developing nations. In the meantime, the consumption of renewable energy, access to clean energy, and the creation of green sector jobs have failed to stimulate economic growth and improve welfare in developing countries; rather, they persist in placing a strain on the economy and overall well-being. The negative effects of CO2 emissions on economic growth and long-term welfare are significant.